Perbedaan Hasil Tangkapan Bagan Perahu Dengan Menggunakan Lampu Petromak dan LED di Desa Boneatiro Kecamatan Kapontori - Maliyati, Maliyati; Arami, Hasnia; Alimina, Naslina; Kamri, Syamsul (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2023)
Boat liftnet is a fishing gear that is classified into the lift net group. The main part of this fishing gear consists of nets and fish collecting tools in the form of lights. This study aims to determine the types of boat liftnets caught using petromax lamps and LED lights; find out the number of catches on boat liftnet using petromax lights and LED lights and to find out the differences in catches on boat liftnet between those using petromax lights and LED lights in Kapontori Water. The research was carried out from July to September 2022 using experimental fishing techniques. The data were collected consists of the total weight of the catch and the types of fish caught on each fishing for 20 trips. The results showed that the types of catches of boat liftnet using LED lamps were more diverse than those using petromax lamps with a total of 13 species of fish obtained by LED lamps and 9 species of petromax lamps. The number of catches on boat liftnet that use LED lights is higher than of boat liftnet that use petromax lights. The total catches of the net using LED lights were 875.1 kg and the petromax lights were 49.13 kg with the dominant catch being the same species of anchovy (Stolephorus sp), there were differences in the catches of the boat liftnets using petromax lights and LED lights. LED lamps has more catches than petromax lamps